The The Role of the Governor in the Local Government Administration System in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2023)
Regional autonomy was born as an interesting idea as a form of correction of the style of government and the relationship between the center and the regions which is centralized, exploitative and far from democratic values ​​which are currently the mainstream of the prevailing political system in the world. 1.The Role of the Governor Philosophically, Based on the various explanations above, it can be concluded that the philosophical reconstruction of the position and role of the Governor must be based on the spirit of the existence of the Governor to safeguard the Unitary State of the Republic of Indonesia so that therefore the role and position of the Governor must be clear, namely as the Representative of the Central Government in the regions and As Regional Head. 2.Theoretical Role of the Governor, Governors must guarantee the implementation of the vision and mission of the central government, especially general administration tasks such as national stability and integration, government and development coordination, and supervision of district/city government administration. As a consequence, a systematic arrangement is needed that describes a tiered relationship, including supervision, guidance, and coordination of administration and development in districts/cities. 3.The Normative Role of the Governor, Government that involves the involvement of various parties in an area based on the aspirations of the local community, then government affairs which are the authority of the central government are partially handed over to regional governments to be managed as their own household affairs. Therefore, philosophically the emphasis on regional autonomy remains at the district/city level, this is based on the possibility of a federal concept occurring if regional autonomy is emphasized at the provincial level but the Governor is given a bigger role and stronger authority as a representative of the central government in especially in relation to supervision and budget allocation. Keywords: Regional Autonomy, Role of the Governor